KEDUDUKAN SAKSI VERBALISAN DALAM KITAB UNDANG-UNDANG HUKUM ACARA PIDANA. - NABABAN, LIA DANIATI; ', Erdianto; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The verbal witness is a witness from the investigator where his presence in court has not been regulated in the Criminal Procedure Code, but is often presented in court when the defendant revokes all or part of the investigation report (BAP) which has been made before the investigator in the hearing. The purpose of this thesis, namely; first, the validity of the testimony of verbal witnesses and their relationship with Article 184 of the Criminal Procedure Code of legal evidence; secondly, the extent to which the testimony of verbal witnesses influenced the judges' decision in the present trial in Indonesia. This type of research is normative legal research, namely research on legal systematic, where research on legal systematics is the study of certain legislation or written law. The aim is to establish identification of the fundamental terms of rights and obligations, legal events, legal relations and legal objects. From the results of the study and discussion it can be concluded that first: the testimony of the verbalist witness will be valid if given under oath and by the testimony judge of the verbalist witness can be used as evidence of evidence in court; second, the testimony of the verbal witness is limited to what is recorded by the investigator during the investigation process so that it becomes the sole responsibility of the judge to conclude the abrogation of the defendant's BAP is acceptable or not by assessing the suitability of the testimony of the witness of verbalism with other evidence presented in the hearing. Suggestion of the writer, first: the witness of verbalism should at the time of giving testimony in the hearing to give an honest statement considering his testimony will be used by the judge as evidence of evidence in the hearing. Secondly: the judge should possess the skills and legal skills and mature mastery skills of the subtlety of the proof so that if the defendant revokes the BAP that has been made before the judge's investigator will be able to consider by judging the suitability of the evidence presented in court.